Global Patterns in the Motivations and Behaviors of Tournament Anglers Targeting Bedding Bass. (10th April 2018) - Hargrove, John S.; Allen, Micheal S.; Weyl, Olaf L. F.; Crandall, Chelsey A. C.; Austin, James D.
Abstract: Angling for adult black bass Micropterus spp. as they defend nests containing eggs or fry (i.e., bed‐fishing) has drawn concerns from fishery managers and anglers due to negative impacts on reproductive success. Research efforts, however, have failed to consider bed‐fishing scenarios other than male‐directed targeting, which may inaccurately reflect angler behaviors. To gain insights into the behaviors, motivations, and attitudes associated with bed‐fishing across a large extent of the global distribution of black bass, we surveyed tournament anglers from the southeastern United States and South Africa (where black bass were introduced in 1928). Responses from 440 black bass tournament anglers indicated that during the reproductive season nearly half of all anglers spent 50% or more of their time bed‐fishing and that larger, female fish were preferential targets. Overall, the responses from U.S. and South African anglers were very similar, but significant attitudinal differences were associated with the perceived impacts of bed‐fishing on adult reproduction and juvenile production. Our results suggest that there are commonalities among the preferences and behavior of anglers from disparate geographic regions, and we highlight the need for future research on the impacts of size‐ and sex‐selective bed‐fishing of basses.